On the possible mantle nature of the long-wave Central-European magnetic anomaly - Pashkevich, I.K.; Orlyuk, M.I.; Marchenko, A.V.; Romanets, A.A.; Tsvetkova, T.A.; Bugayenko, I.V. (Geofizicheskiy Zhurnal, 2020)
This paper presents the results of a comprehensive analysis of geological and geophysical data, carried out to substantiate the existence and nature of transition class of magnetic anomalies produced by the Earth’s core and the lithosphere. This class of anomalies with a wavelength of 2000—4000 km belongs to the overlap region of the geomagnetic field spectra of the core and the lithosphere, and therefore their separation is arbitrary. The original technology of identifying the lithospheric component developed by the authors is based on one of the fundamental principles of geomagnetism — the change in time and space of the Earth’s core field and the stable position of the lithospheric anomalies. The lithospheric component containing anomalies with a wavelength of more than 2400 km was separated from the main geomagnetic field ВIGRF-12. The subject of our research is the submeridional Central European magnetic anomaly of this class, traced from the northern coast of Europe to the edge of the East Saharan mesocraton in Africa. To substantiate its mantle nature information was analyzed on tectonic position of the anomaly and distribution of local magnetic anomalies in the crust, relief of the Moho discontinuity, thickness of the lower (mafic) crust, average velocities VР of the crystalline crust. The inhomogeneity of the Earth’s crust cannot explain the anomaly under study, and therefore it is of mantle in nature. The distribution of the physical parameters of the crust and the tectonic position of the anomaly indicate the possible presence of a long-lived transregional lithospheric lineament such as a suture zone along its axis. Generalization of theoretical and experimental data suggests that under certain thermodynamic, reductive-oxidative, and tectonic conditions of the upper mantle, ferrimagnetic minerals (magnetite, hematite, native iron, and alloys of iron with nickel and cobalt) can exist, transform and form again within a wide range of Curie temperatures from 580 °C to 1100 °C. It limitsthe lower boundary of the magnetization stability at a depth of 600—640 km. The most favorable conditions for the origin of such sources are areas of subduction and relics of relatively cold slabs, suture zones and associated with them present-day fluids and plumes. In the area of the anomaly under study, fluids and the Iberian plume were identified from seismic tomographic data, which, in combination with the rise of the bottom of the upper mantle and the presence of inclined high-velocity layers in its low-velocity part, characterize the excited mantle. Thus, the Central European long-wave magnetic anomaly can be interpreted as the total effect of the relicts of primary ferrimagnets formed under the influence of fluidization of the mantle.